The fixABCX Genes in Rhodospirillum rubrum Encode a Putative Membrane Complex Participating in Electron Transfer to Nitrogenase - Edgren, Tomas (American Society for Microbiology, 2004)
In our efforts to identify the components participating in electron transport to nitrogenase in Rhodospirillum rubrum, we used mini-Tn5 mutagenesis followed by metronidazole selection. One of the mutants isolated, SNT-1, exhibited a decreased growth rate and about 25% of the in vivo nitrogenase activity compared to the wild-type values. The in vitro nitrogenase activity was essentially wild type, indicating that the mutation affects electron transport to nitrogenase. Sequencing showed that the Tn5 insertion is located in a region with a high level of similarity to fixC, and extended sequencing revealed additional putative fix genes, in the order fixABCX. Complementation of SNT-1 with the whole fix gene cluster in trans restored wild-type nitrogenase activity and growth. Using Western blotting, we demonstrated that expression of fixA and fixB occurs only under conditions under which nitrogenase also is expressed. SNT-1 was further shown to produce larger amounts of both ribulose 1,5-bisphosphate carboxylase/oxgenase and polyhydroxy alkanoates than the wild type, indicating that the redox status is affected in this mutant. Using Western blotting, we found that FixA and FixB are soluble proteins, whereas FixC most likely is a transmembrane protein. We propose that the fixABCX genes encode a membrane protein complex that plays a central role in electron transfer to nitrogenase in R. rubrum. Furthermore, we suggest that FixC is the link between nitrogen fixation and the proton motive force generated in the photosynthetic reactions.